Identificar el Comportamiento Linfocitario en Bovinos de la ganadería FACIAG-UTB tratados con dos dosis de Auto hemoterapia - Purcachi Gavilánez, Jonathan Rimael (2023)
The present research work was aimed at solving the following problem: Lack of scientific information on lymphocyte behavior in cattle, subjected to treatment with autohemotherapy? The general objective of the research was "To identify the behavior of lymphocytes in cattle of FACIAG-UTB livestock treated with two doses of autohemotherapy". The population for this study was 73 cattle of which 12 cattle were taken into account for the sample of the same to which the study was practiced with Autohemotherapy. Regarding the methodology, this research is experimental under a Completely Random Design (DCA) adapting to the following additive linear model, and using the comparison method through the Tukey 5% test where the test will be applied to the first group with doses of 15 and the second with doses 20 ml of autologous blood for 5 weeks. The results obtained in this research will lead us to know the benefits of treatment with autohemotherapy in cattle, to identify the behavior of lymphocytes and their response in the immune system prior to an increase in them. Key words: Autohemotherapy, autologous blood, lymphocytes, cattle, dose